Pengaruh Kompetensi Aparatur Desa, Budaya Organisasi dan Sistem Pengendalian Internal terhadap Pencegahan Fraud Pengelolaan Dana Desa Dengan Moralitas sebagai Variabel Moderasi: Studi Empiris Pada Kabupaten Karo - Regita Yolanda Br Sinulingga; Muhammad Rizal; Khairunisa Harahap; Kornelius Harefa; Muhammad Ridha Habibi (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2026)
This study examines the prevention of fraud in village fund management in Karo Regency, grounded in Stewardship Theory. It analyzes the influence of village officials’ competence, organizational culture, and internal control systems on fraud prevention, with morality as a moderating variable. Using a quantitative survey method, data were collected from 78 village officials across 26 villages through purposive sampling and analyzed with SEM-PLS 4.1. Results show that village officials’ competence and internal control systems have positive and significant effects on fraud prevention. However, organizational culture has no significant effect. Morality successfully moderates the influence of competence and internal control systems on fraud prevention, but does not moderate the relationship between organizational culture and fraud prevention. The study concludes that effective fraud prevention in village funds requires strong competence and robust internal controls, rather than relying solely on organizational culture and morality.